BASES OF REAL ESTATE TAXATION IN UZBEKISTAN - Toshmamatovich, Tulakov Ulugbek ,; Shafoat o’g’li, Ismoilov Shuxrat (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to imposition of the single real estate tax in the Uzbekistan. In particular, the basic difficulties and positive sides of such reforming are reflected. Developed proposals for the application of real estate tax and the implementation of the principle of justice.